Reconstructing the chronology of the natural and anthropogenic uranium isotopic signals in a marine sediment core from Beppu Bay, Japan - Hodaka Takahashi; Aya Sakaguchi; Karin Hain; Andreas Wiederin; Michinobu Kuwae; Peter Steier; Yuichi Takaku; Shinya Yamasaki; Keisuke Sueki (Heliyon, 2023)
The long-lived U isotopes, 233U and 236U, have been used increasingly in recent years as marine circulation tracers and for identifying sources of uranium contamination in the environment. The sedimentation histories of these two U isotopes in combination with natural 238U were reconstructed for an anoxic sediment core collected from Beppu Bay, Japan, in the western North Pacific Ocean showing good time resolution (less than 2.6 y/sample). The 233U/236U atom ratio showed a prominent peak of (3.20 ± 0.30) × 10−2 around 1957 which can be attributed to the input from atmospheric nuclear weapons tests including thermonuclear tests conducting in the Equatorial Pacific. The integrated 233U/236U ratio of (1.64 ± 0.08) × 10−2 for the sediment was found to be in relatively good agreement with the representative ratio published for global fallout (∼1.4 × 10−2). A prominent increase in the authigenic ratio of 233U/238Ua,s in the leached fraction (1.39 ± 0.11 × 10−11) and the bulk digestion (1.36 ± 0.10 × 10−11) was also observed around 1957. This reflects the input supply of 233U to the seawater which is known to have a relatively constant 238U content. The authigenic 236U/238Ua,s ratio (0.18 ± 0.02 × 10−9) obtained for 1921 increased from the early 1950's to a maximum of (6.59 ± 0.60) × 10−9 around 1962. The variation in this ratio represents well the introduction history of U into the surface environment without site-specific U contamination and the time profile is also consistent with the 137Cs signature. This work thus provides a benchmark for the long-term use of the isotopic U composition as an input parameter for seawater circulation tracers and as a chronological marker for anoxic sediments and sedimentary rocks. Especially the 233U/236U ratio may serve as a key-marker for the new geological age Anthropocene.